"[A] mad excess of love": Hyper-Sympathy, Fidelity, and Suicidality in Mary Shelley's Falkner1. Issue 1 (April 2020) - Square, Shoshannah Bryn Jones
Abstract : Mary Shelley's Falkner depicts a sentimental and self-destructive hero whose extreme feeling leads, however unintentionally, to the death of his beloved. According to Shelley, left unregulated, emotions—and sympathy in particular—have the potential to not only encourage immoral behaviour but to provoke suicidal ideation. Yet, paradoxically, when felt to excess, sympathy can also prevent an individual from acting on her suicidal thoughts and infringe on her basic human liberty, her right to die. Although Falkner longs for death, believing that by destroying himself he will atone for his crime, he is prevented from doing so by the fervent sympathy of his adopted daughter Elizabeth, who will not permit him to take his own life. As this article argues, hyper-sympathy in Falkner is presented in a surprisingly sinister light, for it precipitates criminality, gives rise to suicidal ideation, strips an individual of his autonomy, and prolongs rather than relieves suffering.